Efficacy and safety of once-weekly and twice-weekly bortezomib in patients with relapsed systemic AL amyloidosis: results of a phase 1/2 study - Reece, Donna E.; Hegenbart, Ute; Sanchorawala, Vaishali; Merlini, Giampaolo; Palladini, Giovanni; Bladé, Joan; Fermand, Jean-Paul; Hassoun, Hani; Heffner, Leonard; Vescio, Robert A.; Liu, Kevin; Enny, Christopher; et al. (Blood, 2011)
This first prospective phase 2 study of single-agent bortezomib in relapsed primary systemic AL amyloidosis evaluated the recommended (maximum planned) doses identified in phase 1 testing (1.6 mg/m2 once weekly [days 1, 8, 15, and 22; 35-day cycles]; 1.3 mg/m2 twice weekly [days 1, 4, 8, and 11; 21-day cycles]). Among all 70 patients enrolled in the study, 44% had ≥ 3 organs involved, including 73% and 56% with renal and cardiac involvement. In the 1.6 mg/m2 once-weekly and 1.3 mg/m2 twice-weekly groups, the hematologic response rate was 68.8% and 66.7% (37.5% and 24.2% complete responses, respectively); median time to first/best response was 2.1/3.2 and 0.7/1.2 months, and 78.8% and 75.5% had response durations of ≥ 1 year, respectively. One-year hematologic progression-free rates were 72.2% and 74.6%, and 1-year survival rates were 93.8% and 84.0%, respectively. Outcomes appeared similar in patients with cardiac involvement. Among all 70 patients, organ responses included 29% renal and 13% cardiac responses. Rates of grade ≥ 3 toxicities (79% vs 50%) and discontinuations/dose reductions (38%/53% vs 28%/22%) resulting from toxicities appeared higher with 1.3 mg/m2 twice-weekly versus 1.6 mg/m2 once-weekly dosing. Both bortezomib dose schedules represent active, well-tolerated regimens in relapsed AL amyloidosis. This study was registered at www.clinicaltrials.gov as #NCT00298766.